The mitochondrial genome of the plantpathogenic fungus Stemphylium lycopersici uncovers a dynamic structure due to repetitive and mobile elements - Franco, Mario Emilio Ernesto (2017)
Stemphylium lycopersici (Pleosporales) is a plant-pathogenic fungus that has been associated with a broad range of plant-hosts worldwide. It is one of the causative agents of gray leaf spot disease in tomato and pepper. The aim of this work was to characterize the mitochondrial genome of S. lycopersici CIDEFI-216, to use it to trace taxonomic relationships with other fungal taxa and to get insights into the evolutionary history of this phytopathogen. The complete mitochondrial genome was assembled into a circular double-stranded DNA molecule of 75,911 bp that harbors a set of 37 protein-coding genes, 2 rRNA genes (rns and rnl) and 28 tRNA genes, which are transcribed from both sense and antisense strands. Remarkably, its gene repertoire lacks both atp8 and atp9, contains a free-standing gene for the ribosomal protein S3 (rps3) and includes 13 genes with homing endonuclease domains that are mostly located within its 15 group I introns. Strikingly, subunits 1 and 2 of cytochrome oxidase are encoded by a single continuous open reading frame (ORF). A comparative mitogenomic analysis revealed the large extent of structural rearrangements among representatives of Pleosporales, showing the plasticity of their mitochondrial genomes. Finally, an exhaustive phylogenetic analysis of the subphylum Pezizomycotina based on mitochondrial data reconstructed their relationships in concordance with several studies based on nuclear data. This is the first report of a mitochondrial genome belonging to a representative of the family Pleosporaceae.